Implementation of Construction Safety Management System (SMKK) In Lubuk Sahung-Pondok Baru; SIMP. PUSKESMAS AUR CINA PROJECT - Rossanika, Liza; Amrina, Elita (Peneliti.net, 2024)
This study aims to determine the state of completeness of facilities related to the implementation of the Construction Safety Management System (SMKK) and its application to the Lubuk Sahung – Pondok Baru; Simp. Puskesmas – Aur Cina Project. The results showed that the completeness of K3 facilities available in the Lubuk Sahung-Pondok Baru; Simp. Puskesmas – Aur Cina Project has a value of 68%. This value is categorized as medium. Application of SMKK in the Lubuk Sahung-Pondok Baru Road Reconstruction/Improvement project; Simp Street. Puskesmas – Aur China is good enough, only the awareness of workers in using PPE is still low.